The US Labor Market in 2030: A Scenario Based on Current Trends in Supply and Demand - Rebecca Edwards; Fabian Lange (Institute for the Study of Labor (IZA), 2013)
Three fundamental forces have shaped labor markets over the last 50 years: the secular increase in the returns to education, educational upgrading, and the integration of large numbers of women into the workforce. We modify the Katz and Murphy (1992) framework to predict the structure of the labor market in 2030. Even though the share of educated females in the workforce will grow rapidly, the supply response will not suffice to offset the trend in demand towards skilled, female labor. Wage growth over the next 20 years will continue to favor college educated workers and in particular college educated females.
Keywords: J11; J21; J22; J23; J31; 330; wage growth; trends in labor demand and supply